T3 Human rhinovirus impairs the innate immune response to bacteria in monocyte derived macrophages from patients with chronic obstructive pulmonary disease. (15th November 2016) - Finney, LJ; Belchamber, KBR; Mallia, P; Johnston, SL; Donnelly, LE; Wedzicha, JA
Abstract : Introduction: Exacerbations of Chronic Obstructive Pulmonary Disease (COPD) are associated with accelerated disease progression, hospitalisation and death. Respiratory viruses are identified in approximately half of all exacerbations. We have previously found that human rhinovirus infection leads to a secondary outgrowth of bacteria which is associated increased exacerbation severity. The mechanisms of how HRV increases risk of secondary bacterial outgrowth are unknown. Hypothesis: We hypothesised that HRV infection impairs phagocytosis of bacteria by monocyte derived macrophages (MDM) which may lead to an increased risk of secondary bacterial outgrowth during COPD exacerbations. Methods: Participants were recruited from the London COPD Cohort. MDM were generated by culture in GM-CSF or M-CSF for 12 days. MDM were incubated with HRV 16 for 24 hours at increasing multiplicity of infection (MOI) 0.5–10 for 24 hours or poly-IC at increasing concentrations 0–300 µg/ml. Phagocytic capacity was then assessed by incubating MDMs with fluorescently labelled heat killed Haemophilus influenzae or Streptococcus pneumoniae for 4 hours and uptake measured by fluorimetry. The pro-inflammatory cytokine CXCL-8 and anti-inflammatory cytokine IL-10 were measured by ELISA according to the manufacturer's instructions. Results: HRV16 impaired phagocytosis of H. influenzae (HRV (MOI of 5) 2.84 ± 0.92 vs media control 4.36 ± 1.06 RFU × 10³ n = 8, p = 0.01) and S. pneumoniae (p < 0.01) by MDM in a virus-dose- dependent manner without impairing cell viability. HRV16 alone induced CXCL-8 and IL-10 release from MDM compared to media alone. HRV16 (MOI 5) significantly impaired IL-10 response to H. influenzae compared to media alone (0.59 (0.33–0.96) ng/ml vs 1.83 (1.11–3.00) ng/ml respectively, n = 6, p = 0.03) and impaired CXCL-8 response to H influenzae compared to media alone 4.41 (3.45–5.85) ng/ml vs 24.65 (11.63–29.77) ng/ml respectively, n = 5, p = 0.01). Poly-IC impaired phagocytosis of H. influenzae in a concentration-dependent manner without significantly impairing cell viability. Poly IC alone also induced IL-8 release from MDM. Conclusions: HRV impairs phagocytosis of bacteria by MDM in COPD and impairs cytokine response to bacteria which may inhibit neutrophil influx and prevent resolution of inflammation. This may lead to an outgrowth of bacteria and prolonged exacerbations in COPD.